Unity and diversity turko-mongol world: Kultobe settlement as a crossroads of religions and cultures - Khazbulatov, Andrey; Nekhvyadovich, Larisa; Shaigozova, Zhanerke (Pedagogy and Psychology, 2021)
The culture and art of the Turkic-Mongolian world is one of the deepest subjects of the humanities, which again and again take the attention of researchers. The historical vicissitudes, which was formed over many centuries, contributed to spread Zoroastrianism, Manichaeism, Buddhism, Christianity and Islam in the Great Steppe. We can see it in unique art artifacts and architectural structures. This article is devoted to unity and diversity study of the Turkic-Mongolian world, based on the example of the Kultobe settlement, which is presented by the authors as the oldest peculiar crossroads of religions and cultures. The Kultobe settlement, during scientific years and archaeological research by the Kazakh Research Institute of Culture, truly unique material evidence (architectural objects and artifacts) was discovered, which allows us to speak of this unique monument of archeology as one of the “crossroads” of religions and cultures in the Turkic-Mongolian world. The Kultobe settlement and later Yasi, a spiritual and religious place, developed -Turkic Sufism. The famous Sufi and poet K.A.Yasawi lived and preached here. The work was prepared under the state assignment of the Altai State University, project №748715Ф.99.1.ББ97АА00002 “The Turkic-Mongolian world of the “Greater Altai”: unity and diversity in history and modernity.”